KEMATANGAN EMOSI, KONSEP DIRI DAN KENAKALAN REMAJA - Lis Binti Muawanah; Herlan Pratikto (University of Merdeka Malang, 2012)
Abstract Emotionol maturity, self-concept, and juvenile delinquency examined on 120 middle adolescents. Researcher developed three research instrament of measurement, namely the scale of juvenile delinquency, the scale of emotional maturity, and the self-concept scale. Data analyzed with the multiple regression. Varians proportion of juvenile delinquency can be explained through the emotional maturity and self-concept. Emotional moturity and self-concept simultaneously predict delinquency in undirectional and linear relationships; Emotional maturity is a psychological capacity that has the potential to allow a decline in juvenile delinquency; Self-concept is a psychological capacity that no potential to allow the reducticn or increase in juvenile delinquency. Juvenile delinquency data not normally distributed and relativety high. Prediction research, findings apply only to groups of adolescents with high delinquency, rates. The findings are discussed in terms of their implications for middle adolescent in context. Key words: maturity of emotion, self-concept, juvenile delinquency